Vitamin C Pretreatment Enhances the Antibacterial Effect of Cold Atmospheric Plasma - Helgadóttir, Saga; Pandit, Santosh; Mokkapati, Venkata R. S. S.; Westerlund, Fredrik; Apell, Peter; Mijakovic, Ivan (Frontiers in Cellular and Infection Microbiology, 2017)
Bacterial biofilms are three-dimensional structures containing bacterial cells enveloped in a protective polymeric matrix, which renders them highly resistant to antibiotics and the human immune system. Therefore, the capacity to make biofilms is considered as a major virulence factor for pathogenic bacteria. Cold Atmospheric Plasma (CAP) is known to be quite efficient in eradicating planktonic bacteria, but its effectiveness against biofilms has not been thoroughly investigated. The goal of this study was to evaluate the effect of exposure of CAP against mature biofilm for different time intervals and to evaluate the effect of combined treatment with vitamin C. We demonstrate that CAP is not very effective against 48 hour mature bacterial biofilms of several common opportunistic pathogens: Staphylococcus epidermidis, Escherichia coli and Pseudomonas aeruginosa. However, if bacterial biofilms are pre-treated with vitamin C for 15 minutes before exposure to CAP, a significantly stronger bactericidal effect can be obtained. Vitamin C pretreatment enhances the bactericidal effect of cold plasma by reducing the viability from 10 % to 2 % in E. coli biofilm, 50 % to 11 % in P. aeruginosa and 61 % to 18 % in S. epidermidis biofilm. Since it is not feasible to use extended CAP treatments in medical practice, we argue that the pre-treatment of infectious lesions with vitamin C prior to CAP exposure can be a viable route for efficient eradication of bacterial biofilms in many different applications.